Sitting On Top of the World: Meridional Media, Arctic Condescension, and Northern Techniques - Allen, Jamie (2018)
Based on experiences, stories, and representations of circumpolar regions, what follows examines (dis)orienting ways of technical knowing that align longitudinally. Jamie Allen's writings map the relations, tensions, and collusions between material and knowledge infrastructures and actual and modelled ecologies, and Merle Ibach prepares images to accompany these. https://technosphere-magazine.hkw.de/p/Sitting-On-Top-of-the-World-Meridional-Media-Arctic-Condescension-and-Northern-Techniques-eZByEn6WX496buSKmjvQhf